“I just want them to learn.” The intended role of Teacher’s Book shaped by its writer’s understanding of the local EFL teachers - Li, Weiying; Zhang, Jianqin; Sang, Zilin (Frontiers in Psychology, 2022)
These past few years, programs of local EFL (English as a foreign language) textbook development were launched to adapt to the newly issued English Curriculum Standards in China. Writing corresponding Teacher’s Books was a part of the work. How to write Teacher’s Book that exactly meets the non-native speaker (NNS) language teachers’ needs was a long-time concern by Coleman (1986) and Cunningsworth (1995)，but few studies have been conducted to address the concern empirically. The present research with a single case design closely examined how a local Teacher’s Book writer’s understanding about the local EFL teachers shaped the role of Teacher’s Book by looking into the process of an ELT (English language teaching) materials development program in China. It sought to find answers to what the Teacher’s Book writer knew about the local EFL teachers, and how this understanding influenced his conceptualization of Teacher’s Book development. The findings show that the writer’s understanding about local teachers’ conventional teaching practice, and their content knowledge (CK) and pedagogical content knowledge (PCK) plays a decisive role in shaping the Teacher’s Book into materials that provide educational affordances to overcome the local EFL teachers’ weaknesses and inject innovation into their conventional practice. The findings have implications for both the international and local ELT materials development programs to compile Teacher’s Book for better local use.